The exopolysaccharide Psl–eDNA interaction enables the formation of a biofilm skeleton in Pseudomonas aeruginosa. Issue 2 (23rd January 2015) - Wang, Shiwei; Liu, Xi; Liu, Hongsheng; Zhang, Li; Guo, Yuan; Yu, Shan; Wozniak, Daniel J.; Ma, Luyan Z.
Summary A hallmark of bacterial biofilms is a self‐produced extracellular matrix of exopolysaccharide, extracellular DNA (eDNA) and proteins that hold bacterial cells together in the community. However, interactions among matrix components and how the interactions contribute to the formation of matrix remain unclear. Here, we show the physical interaction between exopolysaccharide Psl and eDNA, the two key biofilm matrix components of the opportunistic pathogen Pseudomonas aeruginosa. The interaction allows the two components to combine to form a web of eDNA–Psl fibres, which resembles a biofilm skeleton in the centre of pellicles to give bacteria structural support and capability against agents targeted on one matrix component. The web of eDNA–Psl fibres was also found in flow‐cell biofilms at microcolonies initiation stage. The colocalization of eDNA or Psl fibres with bacterial cell membrane stain suggests that fibre‐like eDNA is likely derived from the lysis of dead bacteria in biofilms. Psl can interact with DNA from diverse sources, suggesting that P. aeruginosa has the ability to use DNA of other organisms (such as human neutrophils and other bacterial species) to form its own communities, which might increase the survival of P. aeruginosa in multispecies biofilms or within a human host.